Comparison of some morphological characteristics of native turkish dog breeds - Metin Erdoğan; Cafer Tepeli; Ceyhan Özbeyaz; Mine D. Akbulut; Cevdet Uğuz (Eurasian Journal of Veterinary Sciences)
Aim: The objective of this study was to compare some morphological characteristics of the native Turkish dog breeds. Materials and Methods: A total of 130 dogs, comprised of 30 Kangal Shepherd Dogs, 33 Akbaş Shepherd Dogs, 14 white Kars Shepherd Dogs, 23 black Kars Shepherd Dogs, and 30 Turkish Tazı, were used in the study. Body measurements such as shoulder height (SH), rump height (RH), body length (BL), front chest width (FCW), chest depth (CD), chest girth (CG), head girth (HG), head length (HL), and muzzle length (ML) were taken in different aged dogs. Results: Morphological characteristics, specifically shoulder height (SH), rump height (RH), body length (BL), front chest width (FCW), chest depth (CD), chest girth (CG), head girth (HG), head length (HL), and muzzle length (ML), were 76.20, 76.26, 69.19, 26.32, 33.46, 94.01, 58.43, 35.50 and 14.76 cm in Kangal Shepherd Dogs; 68.11, 68.77, 61.97, 22.32, 28.66, 80.96, 51.88, 31.56 and 13.72 cm in Akbaş Shepherd Dogs; 66.63, 67.91, 64.55, 22.09, 27.44, 80.11, 55.36, 31.94 and 13.14 cm in white Kars Shepherd Dogs; 66.99, 68.05, 63.28, 21.06, 27.90, 78.52, 54.93, 30.39 and 13.16 cm in black Kars Shepherd Dogs; 62.45, 62.59, 51.44, 16.76, 25.30, 65.27, 35.87, 27.19 and 11.72 cm in Turkish Tazı, respectively. In conclusion, the study showed that the measurements of these traits in the Kangal Shepherd Dog were significantly greater than those in the other Turkish dog breeds (p<0.05). Conclusion: Detail studies are needed to determine breed characteristics and genetic characteristics of Turkish Tazı.